Effects of zinc nanoparticles and proline on growth, physiological and yield characteristics of pea (Pisum sativum L.) irrigated with diluted seawater - Hossam S. El-Beltagi; Kholoud Ahmed El-Naqma; Mohammed I. Al-Daej; Mohamed Mabrouk El-Afry; Wael F. Shehata; Mohamed Fathi El-Nady; Ahmed Mahmoud Ismail; Wafaa Fawzy Eltonoby; Adel A. Rezk; Metwaly Mahfouz Salem Metwaly (Cogent Food & Agriculture)
Using diluted seawater for irrigation presents a potential solution to tackle water scarcity and optimize water usage in regions where there is a shortage of freshwater resources. Therefore, the objective of current study was to assess the efficacy of proline and zinc nanoparticles (ZnO-NPs), either alone or in combination, in alleviating adverse impacts of diluted seawater irrigation [2.5% (EC, 1.6) and 5% (EC, 2,3)] on the growth and productivity of pea plants (cv. Master B) during the winter seasons of 2022/2023 and 2023/2024. The results indicated that irrigation with diluted seawater had negative effects on several growth parameters of peas, including plant height, leaf area, plant dry weight, chlorophyll pigment (Ch a, Ch b, and total Ch) content, and seed chemical composition. In contrast, foliar application of ZnO-NPs, proline, or their combination improved plant growth, productivity, oxidative enzyme activities, net photosynthesis, and phenolic compound content under salinity stress. Furthermore, these treatments positively influenced the content of essential nutrients (NPK), vitamin C, carbohydrate percentage, and crude protein in pea seeds. The combination of ZnO-NPs and proline yielded the highest values for most parameters during the experimental seasons. Overall, the interaction between ZnO-NPs and proline showed promise in enhancing pea plant growth and productivity, especially in environments characterized by salt stress.